2021
DOI: 10.1007/s12553-021-00603-0
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and health: examining the relation of sleep to burnout and well-being using a consumer fitness tracker

Abstract: Sleep is an essential requirement for both physiological and psychological functioning and has an impact on various health parameters. The present study aimed to examine how quantity and quality of sleep predicts burnout and well-being by using both self-reported and objectively collected sleep data. The participants were 104 white-collar workers who wore a fitness tracker for 14 consecutive days and filled out a questionnaire about sleep, burnout, and well-being. The results showed that self-reported sleep qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Finally, this study found that burnout has a negative effect on sleep quality. These findings support the findings of previous research belonging to Grossi et al (2021) and May et al (2020), which state that burnout has a negative relationship with the quality of sleep one has. Grossi et al (2021) stated that sleep is very important for human life and has a restorative function for the physical and psychological when it is associated with the JD-R Model.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, this study found that burnout has a negative effect on sleep quality. These findings support the findings of previous research belonging to Grossi et al (2021) and May et al (2020), which state that burnout has a negative relationship with the quality of sleep one has. Grossi et al (2021) stated that sleep is very important for human life and has a restorative function for the physical and psychological when it is associated with the JD-R Model.…”
Section: Discussionsupporting
confidence: 92%
“…The latest publication by Yella and Dmello (2022) found that burnout predicts poor sleep quality. Grossi et al (2021) stated that sleep is essential for human life and has a handling function for the physical and psychological. Based on the JD-R model, good sleep quality can restore the impact of the exploitation of work resources, which is the impact of job demands and workload (Bakker & Demerouti 2007), Based on this, the researcher proposes a hypothesis, H5: There is a negative effect between burnout and sleep quality.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…From the national costumes, we can observe the material and spiritual development of this nation, so it has extremely important cultural research value [8]. As a special consumption of clothing consumption, it has its own unique personality in many fields such as energy value, usage, and energy demand [9].…”
Section: Introductionmentioning
confidence: 99%
“…Seafarers reported using medication and increased coffee consumption to deal with poor sleep quality and it was previously shown that sleep quality predicts both burnout and well-being. 26 Therefore, these answers to the open-ended question represent participants’ unique perspective which needs to be taken into account when planning different interventions.…”
Section: Discussionmentioning
confidence: 99%
“…24 A meta-analysis 25 indicates that lack of sleep is the cause of various mental health problems, like depression, anxiety, rumination, stress, and symptoms of psychosis. According to the research of Grossi et al, 26 sleep quality, but not sleep quantity, was a significant predictor of both well-being and burnout. Given that this paper deals with seafarers’ sleep and some possible antecedents and outcomes of seafarers’ sleep, the constructs used in this research and their relationships are presented in the following text.…”
Section: Introductionmentioning
confidence: 92%